A CROSS-SECTIONAL STUDY TO ASSESS KNOWLEDGE, ATTITUDES, AND PRACTICES REGARDING RABIES IN RURAL UJJAIN - AANCHAL BIJLWAN; Archit Khardenavis; Sapna Rathore (Global Journal of Public Health Medicine)
Introduction: Rabies, one of the earliest recognized infectious diseases, impacts all mammals. It is caused by a type of virus known as rhabdovirus and is primarily transmitted to humans through bites from domestic dogs. In developing countries, particularly, canine rabies remains a significant concern for both the economy and public health, leading to approximately 55,000 deaths annually. A cross-sectional study design was employed to comprehensively assess the Knowledge, Attitudes, and Practices (KAP) regarding rabies within the rural population of a selected village in Ujjain. Methods: A cross-sectional study design was employed to comprehensively assess the Knowledge, Attitudes, and Practices (KAP) regarding rabies within the rural population of a selected village in Ujjain. Results: The analysis of the participant demographics reveals a balanced gender distribution, with 51.6% female and 48.4% male participants. In terms of age, 40% of the participants are under 35 years old, while 60% are aged 35 and above. Education-wise, the majority have completed secondary education (45.3%), followed by primary education (31.3%), while 11.7% have no formal education, and the same percentage have attained graduation or higher education. Regarding occupation, agriculture emerges as the most common occupation, with 39.1% of participants engaged in it, followed by labourers (19.5%), homemakers (23.4%), business (10.2%), and others (7.8%). Conclusion: Importance of targeted interventions to improve health literacy and practices among specific groups, particularly females, younger individuals, and those in lower education and labour-intensive occupations is the need of the hour.